Countenance Model Evaluation of A Non-Graded School: Basis for Program Sustainability - Eunice Mareth Querol Areola, PhD HSG; Maria Urduja C. Galang (Journal of Sustainable Community Development (JSCD), 2023)
This study evaluated the non-graded system as applied in a school in UST Angelicum College. The school understudy is a Catholic and Dominican school that has offered a non-graded system of education since 1972. A non-graded school's key element is removing grade designation's identity, allowing students to progress at their pace with no set time for when they move on. Authentic assessments replace letter or number grades. The evaluative research utilized the Stake's Countenance Model of Evaluation. This model describes and judges what is being evaluated under the three stages of implementation: antecedents, transactions, and outcomes. Data were collected and analyzed based on the descriptive and judgment matrices of the model. Participants of the study were lay administrators, learning facilitators, enrolled learners from YS 5 to YS 11, parents of currently enrolled learners from YS 2 to YS 11, and former facilitators of the school. An array of multiple instruments was used in each stage of program implementation for evaluation. Following the collection of qualitative and quantitative data, the data was analyzed using the countenance model. Intents and data observations and standards of judgment were then organized for each implementation stage of a matrix to determine the congruence of the data's intents and observations to the school practice. The study's findings revealed a satisfactory congruence in the three stages of implementation: antecedents, transactions, and outcomes. Based on these findings, a re-imagination of the Angelicum System is proposed. This can serve as the institutional model to follow in carrying out the school's unique system and ensure that congruence between the school's intents and practices is preserved through the years. The strategic plan is likewise recommended to be utilized for the next five years to ensure a comprehensive development, management, and sustainability of the redefined key priorities of a non-graded school. Further studies on achievement effects of the non-graded system, teaching approaches in a non-graded classroom, and non-graded education reforms may be conducted to improve and expand the essential features of a non-graded system that other academic institutions may adopt.